Comparative Sensitivity of Polymerase (L) and Nucleoprotein (N) Genes of Rabies Virus - sharma, Pranoti; Singh, Charan Kamal; Narang, Deepti; Trivedi, Mahesh S (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Ante-mortem diagnosis of rabies is highly desirable for veterinary as well as medical fraternity. Recently with advent of molecular approaches it has become feasible using saliva skin and urine samples. However, there has been ambiguity about the comparative efficacy of molecular approaches while targeting different genes of rabies virus. Thus, present study was envisaged to diagnose rabies from skin samples using HnRT-PCR. The sensitivity of HnRT-PCR was compared by targeting nucleoprotein (N) gene and polymerase (L) gene of virus in rabies suspected animals. Skin biopsy samples were collected for ante mortem diagnosis of rabies from rabies suspected animals presented to the Veterinary Clinics, GADVASU, Ludhiana, Punjab over a period of 12months. FAT on brain tissue of the same animals was used as a reference method to establish true positive and true negative cases. Out of 34 skin samples, the sensitivity of molecular detection of rabies by L-gene primers was 95.83% and that by N-gene primers was 83.33%, accuracy of 98.05% and 88.88% was found while targeting L gene and N gene respectively, whereas both the approaches detected rabies from skin samples with 100% specificity. Thus, HnRT-PCR targeting L-gene is more sensitive than N-gene for ante mortem detection of Rabies virus RNA from skin samples.